2014
DOI: 10.1111/kykl.12068
|View full text |Cite
|
Sign up to set email alerts
|

Does Aid Promote Donor Exports? Commercial Interest versus Instrumental Philanthropy

Abstract: This paper investigates by means of advanced panel data techniques whether bilateral aid has been successful in promoting bilateral exports to recipient countries during the period [1988][1989][1990][1991][1992][1993][1994][1995][1996][1997][1998][1999][2000][2001][2002][2003][2004][2005][2006][2007] and to what extent changes in aid policies have influenced this relationship. The main novelty of this research is the distinction between tied and untied aid in a multi-donor gravity model of trade and the compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 40 publications
1
19
0
1
Order By: Relevance
“…Therefore, several authors have concluded that a formal tying of aid does not seem to provide additional benefits in terms of donor export levels (Jepma, 1991;Arvin and Baum, 1997;Arvin and Choudhry, 1997). However, Martínez-Zarzoso et al (2015) found that tying status is positively correlated to the effect of aid on donor exports over time (correlation = 0.75), with an even stronger correlation when the percentage of aid tied is higher than 30%; moreover, from 2000 onwards, untying is associated with a decrease in the effect of aid on donor exports.…”
Section: Literature Reviewmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, several authors have concluded that a formal tying of aid does not seem to provide additional benefits in terms of donor export levels (Jepma, 1991;Arvin and Baum, 1997;Arvin and Choudhry, 1997). However, Martínez-Zarzoso et al (2015) found that tying status is positively correlated to the effect of aid on donor exports over time (correlation = 0.75), with an even stronger correlation when the percentage of aid tied is higher than 30%; moreover, from 2000 onwards, untying is associated with a decrease in the effect of aid on donor exports.…”
Section: Literature Reviewmentioning
confidence: 95%
“…In addition, BAIDREST is added to investigate whether aid given by other donors influences an existing bilateral trade relationship between the Netherlands and j. While aid from other donors may lead to additional income that can be spent on imports from all j donors (especially if aid is untied), it might also promote imports from the other donors (see Martínez-Zarzoso et al 2015).…”
Section: Augmented Gravity Model Of Tradementioning
confidence: 99%
“…Early discussions on the aid-trade relationship can be dated back to the transfer paradox, which states that foreign aid can be donor-enriching and recipient-immiserizing due to terms-of-trade effects associated with aid flows (Martínez-Zarzoso et al, 2014). As an income transfer, foreign aid affects the welfare of both the donor and the recipient countries.…”
Section: Transfer Paradoxmentioning
confidence: 99%
“…First, the aidinduced growth implies a greater capacity of the recipient country to absorb foreign products, including those originating from donors (Suwa-Eisenmann and Verdier, 2007). Second, foreign aid can generate good-will and familiarity effects that promote donor's exports (Martínez-Zarzoso et al, 2014). Nonetheless, these effects may take time.…”
Section: Impact On Total Tradementioning
confidence: 99%
“…This paper specifically examines whether aid leads to higher exports from donor to recipient countries. A number of authors have already studied the export channel from a multi-donor perspective (Wagner 2003;Osei et al 2004;Martínez-Zarzoso et al 2014), and the main results point to a non-negligible positive effect. Martínez-Zarzoso et al (2009) andNowak-Lehmann D. et al (2009) focused on the case of Germany and found that German foreign aid has a positive and significant effect on German exports that is more than proportional in the long run.…”
Section: Introductionmentioning
confidence: 99%